Insights into the effects of liquidity in profitability on the Portuguese hotels - Pratas, Gonçalo Narciso (2022)
This paper analyses the Liquidity levels of Portuguese Hotels with four and five stars, and its impacts on the Profitability. Based on a sample with 27 Hotel companies fromPortugal, for periods 2020 and 2019,the findings suggest that Liquidity is not associated with Profit ability. Despite this conclusion, further analysis on the impacts of Covid-19 was conducted, enabling to conclude that its activity was severely affected by the pandemic. The study recommends managers to monitor Liquidity ratios, as these did not suffer a significant change due to “Other Current Assets”, which may be directly related to state subsidies.